From Multipotent Cells to Fully Differentiated Connective Tissue Cells for Regenerative Medicine: Emerging Applications of Mesenchymal Stem Cells - Mobasheri, Ali; Richardson, Stephen M.; Hoyland, Judith A.; Buhrmann, Constanze; Shakibaei, Mehdi (IntechOpen, 2011)
None